Sosiologi Lembaga Pendidikan : Akuntabilitas Sosial Pengelolaan Keuangan Pesantren dalam Membangun Kepercayaan Wali Santri - Isnaefatul Aulita; Muh.Hanif (JURNAL ILMIAH NUSANTARA, 2026)
This article aims to examine the social accountability of pesantren financial management in building the trust of students' parents through the lens of the sociology of educational institutions. The main focus of the article is directed at the claim that the social accountability of pesantren financial management strengthens the trust of students' parents because financial transparency serves as an indicator of the pesantren's credibility, such that payment reports, well-organized record-keeping systems, and openness of financial information reinforce the pesantren's legitimacy as an educational institution based on trust. Field research was conducted using a qualitative approach through observation of payment and financial reporting mechanisms, interviews with administrators and students' parents, and documentation in the form of payment reports, fund usage reports, and standard operating procedures for financial management. The findings show that financial information transparency increases the sense of security among students' parents, reduces the potential for conflict, and strengthens social trust in the pesantren. Using a quantitative approach. The contribution of this article does not stop at case description but also builds a theoretical argument that social accountability in financial management is an important foundation for the legitimacy of Islamic educational institutions and the strengthening of the relationship between pesantren and the community.